A benchmarking approach for enhancing agility in manufacturing environment. (2017) - Potdar, Pavan Kumar; Routroy, Srikanta; Behera, Astajyoti
The agile manufacturing companies have been putting efforts for enhancing the agility along various dimensions to sustain and grow in today's global business arena with volatile market conditions, rapid change in technology, immature and innovative products, ever changing and increasing customer expectations, and intense competition. One should understand and analyse the enablers, impediments and outcomes of agile manufacturing to develop the right strategy(s) to enhance its agility. Although few works have been reported on agility assessment and enhancement in the literature, they are mostly industry specific. Therefore, a generic benchmarking framework for enhancing agility along with step by step implementation process is proposed and discussed in detail. This proposed framework can serve as a road map to enhance agility of agile manufacturing.